Strategi Laut dan Dominasi Maritim Dalam Perang Dunia II: Studi Komparatif Teater Atlantik dan Pasifik - Triyani, Triyani; Putri, Cintya Yelena; Faisal, Muhamad; Prakoso, Lukman Yudho (Publikasi Indonesia, 2025)
This study examines the strategic role of naval power in World War II by comparing the Atlantic and Pacific theaters. The main issue addressed is how maritime dominance influenced the course and outcome of the war, and how naval strategies adapted to geographic and enemy-specific challenges. The research aims to analyze the impact of sea power, the strategic advantages of maritime dominance in logistics and offensives, and to compare the strategic approaches of both theaters. A comparative historical study with a qualitative-analytical approach was employed, based on literature reviews and document analysis. The findings indicate that naval power was crucial for sustaining supply lines and executing military offensives, with a defensive convoy strategy in the Atlantic and an offensive island hopping strategy in the Pacific. These contrasting approaches reflect military flexibility in adapting to terrain and enemy forces. This study confirms that maritime dominance not only shaped tactical victory but also laid the foundation for the postwar global geopolitical order.